Simulation study of flywheel energy storage system - Lai, Shupeng (2012)
The dynamic braking has been a hot topic for years. However, the major limitation of it is the lacking of proper energy storage devices. Currently, the new generation of high efficiency flywheel seems to be a possible solution due to its advantages in charging speed and energy density. In this report, an energy recovery system (ERS) based on flywheel battery will be introduced, simulated and discussed. The discussion includes 3-phases Permanent Magnet Synchronous Machine, Space Vector Power Width Modulation control, PWM chopper circuit, Continuous Variable Transmission (CVT), comparison of simulation and experimental data and energy saving algorithm for electrical vehicle.